Deteksi filariasis dan vektornya di wilayah kerja Dinas Kesehatan Kabupaten Bantul, Daerah Istimewa Yogyakarta - Budi Mulyaningsih; Sitti Rahmah Umniyati; Ernaningsih Ernaningsih; Tri Baskoro Tunggul Satoto; Tridjoko Hadianto; Siti Isti’anah (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
In Bantul, Yogyakarta Special Region there have been reported 6 elephantiasis cases and ware suspected as filariasis. Elephantiasis is classified into two, namely filarial elephantiasis and nonfilarial elephantiasis. Filarial elephantiasis caused by lymphatic filarial worms infection and nonfilarial elephantiasis can be caused by podoconiosis, leprosy, tuberculosis, or chlamydia infection. The aim of the study was to ascertain whether elephantiasis cases are caused by filariasis. Activities carried out in the work area of the Bantul District Health Office in July 2016 i.e.: (1) patient location survey, (2) interviews with patients, their families, and surrounding communities, (3) examination of patients, and (4) observe the environment around the patient's residence to ensure existence of vector mosquito breeding places. This study found two people with elephantiasis, patients from Depok, Gilangharjo, Pandak, Bantul was suspected elephantiasis due to Brugia malayi infection. Patient from Cawan, Argodadi, Sedayu, Bantul was suspected elephantiasis due to podoconiosis. In Cawan found many breeding sites for the Anopheles vagus mosquito.